Does placement sequencing of the auditor's report in Malaysian companies' annual reports matter? - Abdullah, Shamsul Nahar; Mohamad Nor, Mohamad Naimi; Mohamad Yusof, Nor Zalina (Virtus interpress, 2008)
This study investigates whether a firm's management decision to locate the auditor's report in the financial statements is explained by information signaling theory.We posit that a firm that conveys good news is more likely to place its auditor's report at the beginning of the financial statements than at the end, and vice-versa.Based on 698 firms listed on the Bursa Malaysia as on December 31, 2002, we find that majority of Malaysian listed firms in Malaysia place their auditor‟s reports at the beginning rather than at the end of the financial statements.This could be a manifestation of the importance of the auditor‟s report in the financial reporting framework. However, our evidence the type of news, as measured by Tobin's q, ROA and EPS, does not have any association with the location of the auditor's report. Thus, it is concluded that information signaling theory is not supported.